Hypothalamic mitochondria in energy homeostasis and obesity - Guo, Xin; Wu, Lei; Wang, Weiqun; Medeiros, Denis M.; Clarke, Stephen; Lucas, Edralin; Smith, Brenda; Chowanadisai, Winyoo; Lin, Dingbo (My University, 2016)
Obesity, which is largely due to energy imbalance, has emerged as one of the most serious health issues in the world. The hypothalamus is the most important organ to regulate feeding behavior and energy expenditure through nutrient sensing and signal integration from central and peripheral pathways. As the main organelle to produce energy, mitochondria play a critical role in energy homeostasis from the organelle level. Besides providing a platform for the oxidation of fuel substrates, mitochondria are also involved in a variety of cell signaling pathways and modulate energy homeostasis through mitochondrial dynamics. Mitochondrial dysfunction may lead to obesity due to inadequate ATP production, oxidative stress, endoplasmic reticulum stress, and inflammation. ?, ?-carotene-9’,10’-oxygenase2 (BCO2) is a mitochondrial enzyme that catalyzes the asymmetric cleavage of both provitamin A and non-provitamin A carotenoids. This enzyme is localized to the inner mitochondrial membrane, where the electron transport chain is located. Besides the enzymatic function, BCO2 is important for mitochondrial function and is genetically associated with interleukin-18. Moreover, BCO2 protein expression is suppressed in obese and diabetic mice. Given that the important role of BCO2 in mitochondrial structure and function, and the key position of the hypothalamus in energy balance, BCO2 may play a new role in maintaining metabolic homeostasis that has been overlooked before. The mutation of BCO2 might lead to the impairment of whole body energy homeostasis through hypothalamic mitochondrial dysfunction. Here we will be presenting the updates on hypothalamic mitochondria in cellular energy homeostasis and discussing the potential of BCO2 in regulation of hypothalamic mitochondria in health and obesity.
Citation: Guo X, Wu L, Wang W, Medeiros DM, Clarke S, et al.(2016) Hypothalamic mitochondria in energy homeostasis and obesity. Integr Mol Med 3: DOI: 10.15761/IMM.1000209.
Keywords: ?; ?-carotene-9’,10’-oxygenase2 (BCO2); Carotenoid; Energy Homeostasis; Hypothalamus; obesity